IDENTIFICATION OF SOIL MESOFAUNA IN THE ARABICA COFFEE PLANT AREA - Fariz Imam Utomo; Jekti Prihatin; Iis Nur Asyiah (FKIP Universitas Jember, 2019)
One of bio-indicator soil fertility is soil mesofauna. Soil mesofauna is soil organism that have an important role in distributing organic matter in the soil, improving soil physical properties, and increasing soil fertility. If there are more mesofauna in an area of land, the ecological conditions of the land have abundant organic material and have good soil conditions. The purpose of this study was to determine the types of mesofauna found in the soil around Arabica coffee plants. The method for capturing soil mesofauna was with a pitfall trap. The results of the identification of soil mesofauna in Arabica coffee plants on Kalibendo plantations were obtained by several species including the Order of Collembola and Subclass of Acarina. Species of the Order of Collembola was found Pseudoparonella sp., Salina celebensis, Isotomurus balteatus, Lobella sp., Hypogastrura purpurescens, and Sminthurides sp. Whereas from the subclass of Acarina was found the family of Ixodidae.